Effect of TiO2-NPs on microbial-induced calcite carbonate precipitation. Issue 1 (February 2022) - Liu, Jin-Di; Feng, Yue; Zhao, Yan-Yun; Hu, Xiang-Ming; Wu, Ming-Yue; Yu, Xiao-Xiao; Song, Chun-Yu; Zhu, Shu-Cang; Fan, Yi-Jin; Li, Wen-Qi
Abstract: As a dust suppression method, microbial-induced calcium carbonate precipitation technology based on urease-producing bacteria has been widely used on roads; however, due to their low CaCO3 yield, microbial dust suppressants are not used in mining areas. To further improve the dust suppression effect of microbial dust suppressants, a TiO2 -NPs/microbial dust suppressant was developed by adding TiO2 -NPs to the microbial dust suppressant. The results showed TiO2 -NPs improved the bacteria growth and the urease activity. The best formula of microbial dust suppressant was determined to be mineralized bacteria liquid ( OD 600 = 1.7) and TiO2 -NPs 0.06 g/L. The wind erosion resistance tests showed that the dust suppression effect of the TiO2 -NPs/microbial dust suppressant was better than that of the group without TiO2 -NPs. The formation of CaCO3 was verified by Fourier-transform infrared spectrometry (FTIR), Scanning electron microscopy-energy-dispersive X-ray spectroscopy (SEM-EDS) and Transmission electron microscopy-energy-dispersive X-ray spectroscopy (TEM-EDS). X-ray diffraction (XRD) results showed that the crystal forms of the produced CaCO3 were calcite and vaterite. These results indicated that TiO2 -NPs improved the dust inhibition effect of microbial dust suppressants. Graphical Abstract: ga1 Highlights: TiO2 -NPs improved urease activity of urease-producing bacteria. TiO2 -NPs/microbial dust suppressant enhanced wind erosion resistance of coal dust. CaCO3 produced by TiO2 -NPs/microbial dust suppressant was calcite and vaterite.